EVALUATION OF TREATMENT OUTCOMES FOR STAGE IV NON-SMALL CELL LUNG CANCER PATIENTS USING THE PC (PACLITAXEL-CARBOPLATIN) REGIMEN AT THANH HOA PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Lung cancer is one of the most common malignancies and the leading cause of cancer-related mortality. Non–small-cell lung cancer (NSCLC) accounts for approximately 80–85% of all cases. Most patients are diagnosed at stage IV, for whom systemic therapy remains the standard of care. The Paclitaxel–Carboplatin (PC) regimen has been demonstrated to be effective and well tolerated in multiple clinical trials. This study aimed to evaluate the treatment outcomes of stage IV NSCLC patients receiving the PC regimen at Thanh Hoa General Hospital.Patients and Methods: 51 patients with stage IV NSCLC treated with Paclitaxel–Carboplatin at Thanh Hoa General Hospital between January 2023 and June 2024 were included.Results: The overall response rate was 35.3%. The mean progression-free survival (PFS) was 5.6 months, with a median of 6.0 months. Treatment outcomes were significantly associated with performance status, disease stage, and treatment response. Most adverse events were Grade 1–2 and manageable.Conclusion: The Paclitaxel–Carboplatin regimen continues to serve as an effective and well-tolerated first-line treatment option for patients with advanced NSCLC at Thanh Hoa General Hospital.
Keywords: Lung cancer, non–small-cell lung cancer, stage IV, Paclitaxel–Carboplatin.